2012
DOI: 10.1007/s00109-011-0851-2
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK

Abstract: Human anion exchanger 2 (AE2) is a plasma membrane protein that regulates intracellular pH and cell volume. AE2 contributes to transepithelial transport of chloride and bicarbonate in normal colon and other epithelial tissues. We now report that AE2 overexpression in colon cancer cells is correlated with expression of the nuclear proliferation marker, Ki67. Survival analysis of 24 patients with colon cancer in early stage or 33 patients with tubular adenocarcinoma demonstrated that expression of AE2 is correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 32 publications
(32 reference statements)
0
33
1
Order By: Relevance
“…Increasing evidence supports the view that gastrin prevents rather than promotes GC and colon cancer progression. For example, our previous work demonstrated that gastrin/CCKBR inhibits growth of GC and colon cancer cells after long-term treatment with gastrin in vitro and in vivo [15][16][17][18][19][20][21]30]. These contradictory results suggest that gastrin has variable effects on different cancer types and at different pathological stages.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Increasing evidence supports the view that gastrin prevents rather than promotes GC and colon cancer progression. For example, our previous work demonstrated that gastrin/CCKBR inhibits growth of GC and colon cancer cells after long-term treatment with gastrin in vitro and in vivo [15][16][17][18][19][20][21]30]. These contradictory results suggest that gastrin has variable effects on different cancer types and at different pathological stages.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have demonstrated that effects of gastrin on GC cells are mediated by CCKBR [16,17]. To understand the underlying mechanism(s) involved in the synergistic role(s) of gastrin and trastuzumab, CCKBR levels were measured by Western Blot after treatment of SGC7901 and NCI-N87 cells.…”
Section: Upregulation Of Cckbr Protein Levels Through Enhanced Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Five random fields of view were taken for every slide. Staining was quantitatively analyzed using the Axioplan 2 Imaging Analysis System (Zeiss) with KS400 version 3.0, and the results were expressed as the percentage of positively stained tissue area, where <10% expression was considered ''loss'' (À), and >10% expression was designated (þ) (23). The final value was expressed as the ratio of positive-staining cell area to entire cell area.…”
Section: Imaging Analysismentioning
confidence: 99%
“…In human hepatocellular carcinoma AE2 is overexpressed [123] and its inhibition induces apoptosis [124,125]. Induction of AE2 also contributes to colonic carcinogenesis through the activation of the extracellular signal-regulated kinase (ERK) pathway which can be blocked by AE2-targeted small interfering RNA (siRNA) or gastrin treatment [126]. In gastric cancer cells, however, AE2, downregulation of AE2 can be correlated with carcinogenesis which can be blocked by gastrin [127].…”
Section: Accepted Manuscriptmentioning
confidence: 99%